Implementation of the demonstration method to improve understanding of using online learning media - Nadia Almira Jordan; Dwi Nur Amalia (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2022)
Online learning is a method used by schools during the COVID-19 pandemic to anticipate and avoid the spread of disease among students. In practice, there are advantages and disadvantages of online learning that are felt by both students and parents. Students in RT 29 Kelurahan Margasari, Balikpapan City also face difficulties in attending online learning, which impacts the decrease in learning outcomes achievement. Limited access to electronic devices and the lack of understanding to use devices are the basis for issues that affect the online learning process. Training activities on the use of online learning media are carried out to provide an understanding of operating devices, such as laptops and smartphones to access materials through software and collect assignments. An initial survey was conducted as a base for data collection, the team planned several activities according to the conditions of the participants so that the activities can be more precise and can resolve the participants' problems. Through lecture methods, demonstrations, and hands-on practice, this training introduced several applications that can support the online school process. The results of the activities obtained were an increase in knowledge and understanding of elementary school students and parents in recognizing and using several virtual face-to-face support applications and doing homework through the online chatting applications.